Social dialogue in selected countries in the Caribbean : an overview - Greaves, Evelyn (2004)
Presents an overview of social dialogue in five countries of the Caribbean in the decade of the 1990s. Examines the practice of industrial relations; the challenges brought on by globalisation and trade liberalisation; and, the responses of the trade unions, the employers and the government.